Modeling of the Compression Process for Refrigerants R134a and R1234yf of a Variable Speed Reciprocating Compressor - Barroso-Maldonado, J.M.; Belman-Flores, J.M.; Ledesma, S. (Journal of Advanced Thermal Science Research, 2015)
This paper presents a robust computational model to predict the behavior of a variable speed reciprocating compressor, incorporating infinitesimal displacements to calculate state by state according to the piston movement. The philosophy of the model is to consider eight sub internal processes: heat transfer on the suction and discharge internal lines, pressure drop across the suction and discharge valves, expansion, suction, compression and discharge. The input variables are: pressure and temperature on the suction (before starting the compression process), discharge pressure (after the compression process completed) and rotation speed, with this the model is able to compute the output parameters like: mass flow rate, power consumption and discharge temperature. With the development of the model, the behaviors of R1234yf and R134a are analyzed. Then the model is validated with experimental data using these both refrigerants, concluding that the model predict with an error of ±10% for the mass flow rate and power consumption, and with an error of ±1 K for the discharge temperature. In the validation, differences in energy behavior for the two refrigerants are discussed; the compressor with R1234yf as working fluid increases its power consumption and delivers greater mass flow rate with low temperature compared when the working fluid on the compressor is R134a.